Features of Neutrophils From Atopic and Non-Atopic Elite Endurance Runners - Zambonatto, Raquel Freitas; Teixeira, Renata Nakata; Poma, Sarah de Oliveira; da Silva, Eliane Borges; de Almeida, Mariana Mendes; Leite, Gerson dos Santos; dos Santos, Cesar Miguel Momesso; Alves, Heloisa Helena de Oliveira; Gorjão, Renata; Pithon-Curi, Tania Cristina; Carvalho, Celso R. F.; Curi, Rui; et al. (Frontiers in Immunology, 2021)
We collected peripheral blood from thirty-nine elite male endurance runners at rest (24 hours after the last exercise session) and used the Allergy Questionnaire for Athletes score and plasma specific IgE level to separate them into atopic and non-atopic athletes. Neutrophils obtained from atopic and non-atopic athletes were subsequently stimulated in vitro with fMLP (N-formyl-methionyl-leucyl-phenylalanine), LPS (lipopolysaccharide), or PMA (phorbol 12-myristate 13-acetate). Neutrophils from non-atopic runners responded appropriately to LPS, as evidenced by the production of pro (IL-8, TNF-α, and IL-6) and anti-inflammatory (IL-10) cytokines. Neutrophils from atopic elite runners exhibited lower responses to LPS stimulus as indicated by no increase in IL-1β, TNF-α, and IL-6 production. Neutrophils from non-atopic and atopic runners responded similarly to fMLP stimulation, indicating that migration function remained unaltered. Both groups were unresponsive to PMA induced reactive oxygen species (ROS) production. Training hours and training volume were not associated with neutrophil IgE receptor gene expression or any evaluated neutrophil function. Since non-atopic runners normally responded to LPS stimulation, the reduced neutrophil response to the stimuli was most likely due to the atopic state and not exercise training. The findings reported are of clinical relevance because atopic runners exhibit a constant decline in competition performance and are more susceptible to invading microorganisms.